Pengaruh Beban Kerja Terhadap Kinerja Pelaku Usaha UMKM Rafly Cake Di Kecamatan Mambi Kabupaten Mamasa - Anita Anggriani; Nasriah Akil; Ansar H Mulkin Bas (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2023)
This research aims to find out whether workload influences the performance of Rafly Cake MSME business actors in Mambi District, Mamasa Regency. This research method uses Saturated Sampling in taking research samples. This research technique uses simple linear regression analysis of 30 business actors. The results of this research have been tested for validity and reliability, the data analysis method uses simple linear regression analysis techniques and hypothesis testing. The results of research that have been partially tested show that Workload has a positive effect on the Performance of Rafly Cake MSME Business Actors in Mambi District, Mamasa Regency. The conclusion of this research is that workload has a positive effect on the performance of MSME business actors at the Rafly Cake shop located in Mambi District, Mamasa Regency. From the regression results, it is clear that the regression coefficient